Biases in Dynamic Models with Fixed Effects - Nickell, Stephen (Econometrica, 1981)
[It is well known from the Monte-Carlo work of Nerlove that using the standard within-group estimator for dynamic models with fixed individual effects generates estimates which are inconsistent as the number of "individuals" tends to infinity if the number of time periods is kept fixed. In this paper we present analytical expressions for these inconsistencies for the first order autoregressive case.]